Autoantibodies against the autophagic protein microtubule-associated light-chain 3 (LC3): Immunocharacterization of an atypical ANA pattern. (3rd July 2020) - Maellaro, Emilia; Terzuoli, Lucia; Bacarelli, Maria Romana; Del Bello, Barbara; Bizzaro, Nicola; Porcelli, Brunetta
Abstract: Autoantibodies to nuclear and cytoplasmic antigens are commonly detected by indirect immunofluorescence (IIF) on HEp-2 cells, and three major staining patterns (nuclear, cytoplasmic, and mitotic) are distinguished. Here, we report an atypical cytoplasmic pattern, not described so far, observed in the serum of a patient with a controversial diagnosis of systemic lupus erythematosus (SLE). Moreover, for the first time, we have revealed the presence of autoantibodies against the microtubule-associated light-chain 3 (LC3) protein, which plays a key role in the autophagic process. The target antigen has been identified in IIF by means of a competition test using purified anti-LC3 antibodies on HEp-2 cells, and confirmed by Western blot analysis using cellular or recombinant LC3 as antigen, immunoreacted with the patient's serum. The identification of this atypical pattern and the related autoantibody-antigen system sheds new light on autophagy, which is increasingly considered to be involved in the etiopathogenesis of autoimmune disorders, and could contribute to select more personalized therapies.